A kind of self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements and its preparation method and application
By inhibiting the excessive foaming and doping of non-metallic elements of lignin, the problems of irregular shape and low mechanical strength of lignin foam carbon at low glass transition temperature are solved, and efficient preparation of foam carbon is achieved, suitable for a variety of electrochemicals application.
Patent Information
- Application Number
- CN202410547968.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-05-06
AI Technical Summary
Lignin with low glass transition temperature has problems such as excessive foaming, irregular shape, low mechanical strength and low specific surface area when preparing foam carbon, which limits its development in electrochemical energy storage and capacitive deionization applications.
By using inorganic ammonium salt molecules to inhibit excessive foaming of lignin, macroscopic regular, microporous carbon skeletons and high mechanical strength self-supported foam carbon structure are achieved, and high-temperature pyrolysis and non-metallic element doping technology are used to regulate element composition and pores. structure.
The lignin-based foam carbon with regular shape, high mechanical strength and graded pore structure is suitable for supercapacitors, lithium-ion batteries, sodium-ion batteries and other fields, simplifying the process and reducing costs.
Smart Images

Figure CN118343739B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of novel carbon materials, and in particular relates to a self-supporting lignin-based foam carbon doped and modified by heterogeneous non-metallic elements, and a preparation method and application thereof. Background Art
[0002] Lignin is a biomass component with abundant reserves and rich aromatic structures. It has the advantages of wide sources, low cost and renewability. It is considered to be one of the high-performance and sustainable carbon material precursors. Lignin-derived carbon materials mainly include porous carbon, carbon (nano) fiber, foam carbon, etc. Among them, foam carbon is a new three-dimensional porous carbon material composed of pores and interconnected pore walls. Compared with traditional porous carbon powder, it has the advantages of light weight and self-support, and has good application prospects in the fields of electrochemical energy storage and capacitor deionization.
[0003] As a biopolymer, the glass transition temperature (also called glass transition temperature) of lignin represents its transition from a glassy state to a highly elastic state and is also a sign of softening. Especially when lignin is used as the only raw material, the glass transition temperature plays a key role in the preparation of carbon fibers or foam carbons, and has a great influence on pore development and physical and chemical properties. Since most lignin comes from industrial byproducts such as papermaking and biorefining, the glass transition temperature, purity and chemical composition of different types of lignin depend on the specific chemical extraction process. It is reported that the glass transition temperature of most extracted industrial-grade kraft lignin is in the range of 100-150°C. In particular, there are many organic solvent lignins with a glass transition temperature below 100°C [Chao W.; Stephen SK; Richard AV; Lignin-based thermoplastic materials. ChemSusChem, 9(8)(2016)770-783.]. Using lignin as the carbonaceous precursor alone, the microstructure, macromorphology and mechanical properties of the foamed carbon prepared by the atmospheric pressure self-foaming method using lignin in different glass transition temperature ranges are significantly different. Studies have shown that different types of lignin exhibit different foaming states when heated at a low temperature of 350°C, and lignin with a glass transition temperature below 169°C is prone to over-foaming [Wangda Q.; Zizhu Z.; Chen L.; Pengyu H.; Zhongyi M.; Simple, additive-free, extra pressure-free process to directly convert lignin into carbon foams, International Journal of Biological Macromolecules 209(2022)692-702]. Especially for lignin with a glass transition temperature below 150°C, it has significant advantages in the formation of three-dimensional macroporous networks and continuous carbonaceous structures when preparing foamed carbon. However, the thermal flow behavior and thermal decomposition process are difficult to control directly by adjusting the thermal pretreatment parameters. The product has an irregular shape, low mechanical strength and specific surface area, and lacks micro-mesoporous structures suitable for ion adsorption, which hinders its further development and subsequent practical applications such as electrochemical energy storage and capacitive deionization. In addition, compared with traditional powdered porous carbon, self-supporting foamed carbon can avoid the complex electrode preparation process problems in the application process of electrochemical energy storage and capacitive deionization.
[0004] Therefore, developing specific methods for this type of low glass transition temperature lignin to develop new foam carbon materials with specific functions is of great practical significance for realizing efficient value-added utilization of lignin-based foam carbon as self-supporting electrodes. Summary of the invention
[0005] The purpose of the present invention is to provide a self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements and modified, and its preparation method and application in view of the deficiencies of the prior art. In order to overcome the shortcomings and deficiencies of the prior art, the present invention takes lignin with a low glass transition temperature as the research object, and uses inorganic ammonium salt molecules to reasonably inhibit the excessive foaming of such lignin, thereby realizing the construction of macroscopic regularity, microscopic porous carbon skeleton and high mechanical strength self-supporting macroscopic foam carbon; through high-temperature pyrolysis, the element composition, hierarchical pore structure and external defect structure are directional controlled.
[0006] The first purpose of the present invention is to provide a method for preparing a self-supporting lignin-based foam carbon modified by doping with heterogeneous non-metallic elements, by effectively suppressing the excessive foaming phenomenon of low glass transition temperature wood-based foam carbon and realizing heterogeneous nitrogen, sulfur, phosphorus, boron and other non-metallic element doping, thereby preparing an integrated lignin-based hierarchical porous defect-rich foam carbon.
[0007] The second object of the present invention is to provide a self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements, which has the advantages of regular shape, controllable size and thickness, hierarchical pore structure, and rich nitrogen, sulfur, phosphorus, and boron.
[0008] The third object of the present invention is to provide a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element for use in supercapacitors, lithium-ion batteries, sodium-ion batteries, potassium-ion batteries and other fields.
[0009] The fourth object of the present invention is to provide a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element for use in capacitive deionization of seawater or brackish water.
[0010] To achieve the above-mentioned object of the invention, the technical solution of the present invention is implemented as follows:
[0011] A method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element, the method comprising the following steps:
[0012] (1) Selecting lignin with low glass transition temperature as raw material;
[0013] (2) low-temperature drying the low glass transition temperature lignin in step (1) to remove moisture that may be adsorbed on the surface of the lignin, grinding it into a granular homogeneous powder, and sieving it for subsequent use;
[0014] The purpose of screening is to control the particle size of the lignin powder within a narrow size range and remove possible large and hard impurities. Preferably, 200 mesh screening is performed. Preferably, the low glass transition temperature lignin in step (1) is lignin with a glass transition temperature below 150°C; optionally, the lignin with a glass transition temperature below 150°C in step (1) is industrial lignin purchased from papermaking or biorefining; optionally, the lignin with a glass transition temperature below 150°C in step (1) is lignin extracted by fractionating and removing insoluble matter using an organic solvent method, and the solvent used includes but is not limited to an aqueous solution of ethanol. Optionally, the lignin with a glass transition temperature below 150°C in step (1) is lignin extracted from primary biomass using a chemical method, such as from primary biomass such as hardwood, herb, softwood, bamboo, etc. The chemical method includes but is not limited to an organic solvent method, an alkali method, an enzymatic method, etc. More preferably, the low glass transition temperature lignin in step (1) is lignin with a glass transition temperature of about 70°C.
[0015] (3) weighing a certain amount of ammonium salt and the lignin powder treated in step (2), uniformly mixing them, and grinding them into a granular homogeneous powder to obtain a mixture of ammonium salt and lignin; preferably, the mixture is mixed twice at a high speed of 10000 rpm / min in a grinder, the first high-speed mixing is mainly to achieve preliminary uniform mixing of the original ammonium salt and lignin, and the second high-speed mixing is to achieve thorough and uniform mixing of the ammonium salt with a smaller particle size and the lignin;
[0016] (4) placing the mixture of ammonium salt and lignin in step (3) in a crucible or mold, evenly laying and compacting, ensuring that the surface is flat, sealing the top of the crucible or mold with tin foil or making a few holes by yourself, performing heat pretreatment, taking out after cooling, and obtaining a heat pretreatment product; the shape of the crucible or mold includes but is not limited to a cube, a cylinder, etc., preferably a cube-shaped crucible. The heat pretreatment equipment includes but is not limited to heating equipment such as a muffle furnace, and the atmosphere is air or nitrogen. The role of evenly laying and compacting in this step (3) is to remove experimental errors such as the regularity of the product appearance caused by the uneven surface, and improve the product appearance. The compacted mixture helps to maintain the material form under the heat pretreatment conditions, and avoids changes in the physical and chemical properties of the product caused by thermal expansion, contraction or flow caused by external factors; on the other hand, in the subsequent heat pretreatment process, it is conducive to more uniform and rapid transfer of heat to the interior of the mixture, thereby improving the heat treatment efficiency. Sealing with tin foil in step (3) can reduce contact with air, and making a few self-made channels can help release excess volatile substances and guide these volatile substances to be discharged along a specific path, thereby preventing them from accumulating inside the crucible or mold, causing increased internal pressure and uneven thermal pretreatment.
[0017] (5) The pretreated product of step (4) is subjected to high-temperature pyrolysis treatment under a certain atmosphere, and is taken out after being cooled to room temperature to obtain a self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements.
[0018] In the method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element as described above, the grinding in step (2) is performed by ball milling, the ball milling time is 10 min to 60 min, and the ball milling speed is 300 to 1000 r / min. Preferably, the grinding in step (2) is performed by ball milling, the ball milling time is 10 min to 20 min, and the ball milling speed is 400 to 600 r / min. The purpose of ball milling is to make the lignin used in a uniform powdery state to ensure that it can be fully mixed with the ammonium salt later. If the ball milling time is longer than 20 min, or the ball milling speed exceeds 600 r / min, a thermal effect may occur, causing the lignin to partially react in advance; if the ball milling time is shorter than 10 min, or the ball milling speed is less than 400 r / min, a high proportion of oversized particles will result, affecting the difficulty and uniformity of subsequent uniform mixing with the ammonium salt, hindering the full dispersion of lignin in the pretreatment, thereby affecting the molding and pore structure of the foamed carbon. Most preferably, the grinding in step (2) is performed by ball milling, the ball milling time is 10 min, and the ball milling speed is 500 r / min.
[0019] In the method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element as described above, the ammonium salt in step (2) is a mixture of any one or more of ammonium borate, ammonium sulfate, ammonium chloride, diammonium phosphate, ammonium phosphate, etc. The present invention uses ammonium salt molecules to form a steric hindrance effect to enhance the thermal stability of lignin and inhibit the excessive foaming process of lignin with a low glass transition temperature. Since lignin with a low glass transition temperature will be converted from a glassy state to a highly elastic state at a relatively low temperature, the activity of the molecular chain is enhanced, and it is easy to undergo thermal decomposition reaction, which is not conducive to industrial processing. In addition, excessive foaming is likely to occur during the heat treatment process. In view of the problems of poor thermal stability, difficult processing and excessive foaming of lignin, the present invention adopts ammonium salts to achieve the following effects: on the one hand, ammonium salts can form spatial hindrances between lignin molecules, slow down the relaxation and rearrangement of lignin molecular chains during heating, thereby increasing the glass transition temperature of lignin, enhancing its thermal stability and improving its processing performance; on the other hand, ammonium salts form a cross-linked structure with lignin molecules through chemical modification reactions. Such a cross-linked network can fix the microstructure of lignin to a certain extent, so that it can still maintain a good morphology at a higher temperature, and it will not be so easy to expand and break even when heated at a high temperature, thereby inhibiting the excessive foaming phenomenon.
[0020] Preferably, the ammonium salt in step (2) is any one of ammonium sulfate, ammonium chloride and diammonium phosphate.
[0021] In the method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element as described above, the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is (0.1-10):1. Preferably, the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is (1-5):1. If the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is lower than 1:1, the ammonium salt ratio is too low and the product still has excessive foaming; if the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is higher than 5:1, the ammonium salt ratio is too high and the product faces the problem of crushing. Preferably, the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is (2-4):1.
[0022] In the method for preparing a self-supporting lignin-based foam carbon modified by doping with heterogeneous non-metallic elements as described above, the thermal pretreatment heating method in step (4) is a one-step heating mode, a two-gradient heating mode or a multi-gradient heating mode.
[0023] Optionally, the target temperature of the one-step heating mode in step (4) is 240-550° C., and the insulation time is 1-3 hours.
[0024] Optionally, the two gradient heating modes of step (4) are: the first gradient target temperature is 100-240°C, the insulation time is 0.5-2h, and the second gradient target temperature is 240-350°C, the insulation time is 0.5-2h; preferably, the thermal pretreatment heating rate in the two gradient heating modes is 0.2-10°C / min; preferably, the two gradient heating modes of step (4) are: the first gradient target temperature is 150-230°C, the insulation time is 1h, and the second gradient target temperature is 280-360°C, the insulation time is 2h; preferably, the thermal pretreatment heating rate in the two gradient heating modes is 1-5 ℃ / min; preferably, when the ammonium salt in step (2) is ammonium dihydrogen phosphate, the thermal pretreatment heating method in step (4) is a two-gradient heating mode. Specifically, the two-gradient heating modes in step (4) are a first gradient target temperature of 230℃, a heat preservation time of 1h, and a second gradient target temperature of 360℃, a heat preservation time of 2h; the thermal pretreatment heating rate in the two gradient heating modes is 3℃ / min. Under this condition, on the one hand, the ammonium dihydrogen phosphate and lignin system is fully softened near the softening point of lignin, and on the other hand, the potential size shrinkage and surface cracking problems of the thermal pretreatment product are alleviated.
[0025] Optionally, the multi-gradient heating mode in step (4) is a three-gradient heating mode, and the gradient heating mode is that the first gradient target temperature is 100-240°C, the insulation time is 0.5-2h, the second gradient target temperature is 240-350°C, the insulation time is 0.5-2h, and the third gradient target temperature is 360-550°C, and the insulation time is 0.5-2h; preferably, the thermal pretreatment heating rate in the three-gradient heating mode is 1-5°C / min. Preferably, the multi-gradient heating mode in step (4) is a three-gradient heating mode, and the gradient heating mode is that the first gradient target temperature is 150°C, the insulation time is 1h, the second gradient target temperature is 280°C, the insulation time is 2h, the thermal pretreatment heating rates in the first two gradients are both 1°C / min, the third gradient target temperature is 400°C, the insulation time is 1h, and the thermal pretreatment heating rate in the third gradient is both 5°C / min.
[0026] In the above-mentioned method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element, the certain atmosphere in step (5) is nitrogen, argon, carbon dioxide, ammonia, water vapor, etc. Preferably, the certain atmosphere in step (5) is argon or carbon dioxide.
[0027] Preferably, the high temperature pyrolysis method in step (5) is a one-step heating mode or a two-gradient heating mode.
[0028] Optionally, the high-temperature pyrolysis in step (5) is a one-step heating mode, and the target temperature of the one-step heating mode is 600-1200°C. Optionally, the insulation time is 0.5-3h. Optionally, the high-temperature pyrolysis heating rate is 0.5-10°C / min. Preferably, the high-temperature pyrolysis in step (5) is a one-step heating mode, and the target temperature of the one-step heating mode is 1000°C. Optionally, the insulation time is 2h. Optionally, the high-temperature pyrolysis heating rate is 5°C / min.
[0029] Optionally, the high-temperature pyrolysis in step (5) is a two-gradient heating mode, in which the first gradient target temperature is 300-500°C, and the second gradient target temperature is 600-1200°C. The insulation time is 0.5-2h. The first gradient heating rate in the two gradient heating modes is 0.5-10°C / min; the second gradient heating rate in the two gradient heating modes is 3-6°C / min. Preferably, the high-temperature pyrolysis in step (5) is a two-gradient heating mode, in which the first gradient target temperature is 400°C, and the second gradient target temperature is 1000°C. The insulation time is 1h. The first gradient heating rate in the two gradient heating modes is 1°C / min; the second gradient heating rate in the two gradient heating modes is 5°C / min.
[0030] The high-temperature pyrolysis method described above is a two-gradient temperature increase mode. On the one hand, it is to fully decompose the incompletely decomposed ammonium salt or ammonium salt intermediates to produce volatile gas pores; on the other hand, it is to regulate the lignin-based carbon condensation and rearrangement reactions and the electronic configuration of the heterogeneous non-metallic elements doped in the foam carbon matrix.
[0031] Based on the same inventive concept, the present invention provides a lignin-based foamed carbon material obtained by a preparation method of a self-supporting lignin-based foamed carbon modified by doping with heterogeneous non-metallic elements.
[0032] Based on the same inventive concept, the present invention provides an application of lignin-based foam carbon in supercapacitors, lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, electromagnetic wave absorption, heavy metal ion adsorption, catalysis and other fields.
[0033] Based on the same inventive concept, the present invention provides an application of lignin-based foamed carbon in capacitive deionization of seawater or brackish water.
[0034] Compared with the existing technology, the effects and advantages of the present invention are:
[0035] 1. The present invention provides a method for preparing a self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements. By doping with non-metallic atoms to adjust the chemical composition of lignin molecules with a low glass transition temperature, it is beneficial to reasonably control the softening degree of lignin and construct additional defect structures. It is expected to play a positive role in regulating the macro- and micro-structures of the foam carbon matrix (such as macro-shaping, pore size distribution, etc.), and meet the application requirements of electrochemical energy storage, capacitive deionization, etc.
[0036] 2. The present invention provides a method for preparing a self-supporting lignin-based foamed carbon modified by doping with heterogeneous non-metallic elements. Ammonium salts are used to improve the thermal stability of lignin with a low glass transition temperature, and the problem of excessive foaming of lignin with a low glass transition temperature is effectively solved in the thermal pretreatment stage, so as to achieve the construction of a self-supporting macroscopic body with a regular shape, high mechanical strength, and a high temperature pyrolysis stage. Ammonium salts and lignin intermediate products are further used to thoroughly decompose the carbon to promote the development of micro-mesoporous channels in the foamed carbon. At the same time, heterogeneous non-metallic atoms are introduced to achieve high added value utilization of lignin with a low glass transition temperature.
[0037] 3. The method for preparing a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element developed by the present invention is generally applicable to lignin with a glass transition temperature below 150°C, and no additional chemical reagents such as templates, binders, surfactants, activators, etc. are required during the production process.
[0038] 4. The present invention discloses a method for preparing a self-supporting lignin-based foam carbon modified by doping with heterogeneous non-metallic elements. Ammonium salt is directly mixed with lignin to prepare porous defect-rich foam carbon. The preparation process is simple and easy to operate. The thickness, size and shape of the prepared porous defect-rich foam carbon are controllable. It can be directly used as a self-supporting active material in the fields of electrochemical energy storage, electromagnetic wave absorption, heavy metal ion adsorption, catalysis, etc. such as supercapacitors, capacitor deionization, lithium / sodium / potassium ion batteries, without the use of additives such as binders, thereby simplifying the process and greatly reducing the cost of materials and application equipment.
[0039] 5. The self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements prepared by the present invention has a good self-supporting structure, high mechanical strength, and good electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of the sample in Example 1 of the present invention, wherein the left side is the thermal pretreatment product and the right side is the high-temperature pyrolysis product;
[0041] Figure 2 This is a physical picture of the sample in Example 2 of the present invention, wherein the left side is the thermal pretreatment product and the right side is the high-temperature pyrolysis product;
[0042] Figure 3 (a) Cyclic voltammetry curve and (b) constant current charge-discharge curve of the pyrolysis product of Example 2 in Application Example 2 of the present invention;
[0043] Figure 4 The figure is a physical picture of the high-temperature pyrolysis product of the present invention, wherein the left side is the high-temperature pyrolysis product of Example 6, and the right side is the physical picture of the high-temperature pyrolysis product of Example 7;
[0044] Figure 5 This is a physical picture of the thermal pretreatment product in Example 8 of the present invention;
[0045] Figure 6 are SEM images of the products of the present invention, wherein (a) is the SEM image of the product in Example 3, and (b) is the SEM image of the product in Comparative Example 2;
[0046] Figure 7 The physical pictures of the products in Comparative Example 3 of the present invention are as follows: (ac) thermal pretreatment products, (d, e) high temperature pyrolysis products;
[0047] Figure 8 Cyclic voltammetry curves of the products of Example 5 and Comparative Example 3 in Application Example 3 of the present invention as self-supporting electrodes at a scan rate of 2 mV / s;
[0048] Fig. 9 This is a comparison chart of the mechanical strength of the products after high-temperature pyrolysis in Example 6 and Example 7 of the present invention and Comparative Example 3;
[0049] Fig.10 This is a SEM image of the thermal pretreatment product in Comparative Example 4 of the present invention;
[0050] Fig.11 This is a SEM image of the final product in Comparative Example 5 of the present invention;
[0051] Fig.12 This is a physical picture of the product of Comparative Example 6 of the present invention;
[0052] Fig.13 This is a TDS-time diagram of the high-temperature pyrolysis product in Example 1 described in Application Example 1 of the present invention in the application of capacitive deionization. DETAILED DESCRIPTION
[0053] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.
[0055] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0056] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0057] The low glass transition temperature lignin used in the following Examples 1-9 and Comparative Examples 2-3 was purchased from Addis Innovations, USA, and its glass transition temperature is about 70° C. The nitrogen-sulfur-doped lignin-based foam carbon 1, nitrogen-sulfur-doped lignin-based foam carbon 2, nitrogen-sulfur-doped lignin-based foam carbon 3, nitrogen-sulfur-doped lignin-based foam carbon 4, nitrogen-sulfur-doped lignin-based foam carbon 5, nitrogen-sulfur-doped lignin-based foam carbon 6, nitrogen-sulfur-doped lignin-based foam carbon 7, nitrogen-doped lignin-based foam carbon 8, and nitrogen-phosphorus-doped lignin-based foam carbon 9 involved in the following examples are all heterogeneous non-metallic element doped modified self-supporting lignin-based foam carbons referred to in the present invention.
[0058] Embodiment 1:
[0059] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into uniform powder. The ball-milling time was 10 minutes, the ball-milling speed was 500 rpm, and then 200 mesh screening was performed. At room temperature, ammonium sulfate and the above-screened low glass transition temperature lignin powder were mixed at a high speed of 10000 rpm / min in a grinder at a mass ratio of 2:1 for 3 times, each time for 30 seconds, and stayed for 2 minutes in between. Then grind and mix evenly at a high speed of 10000 rpm / min for 4 times, each time for 30 seconds, and stayed for 3 minutes in between to obtain a mixture of ammonium sulfate and lignin; transfer the total mass of 3g of the mixture to a crucible, evenly lay and compact it to ensure that the surface is flat, seal the top of the crucible with tin foil and make a few channels, and place it in the air atmosphere of a muffle furnace for heat pretreatment, and set two gradient heating modes. The first gradient target temperature is 150°C, and the heat preservation is 1h, and the second gradient target temperature is 280°C, and the heat preservation is 2h. 2h, the heating rate was 1℃ / min, and it was taken out after cooling to obtain an integrated lignin-based thermal pretreatment product; the integrated lignin-based thermal pretreatment product was directly placed in a tubular furnace with an argon atmosphere for heating, and two gradient heating modes were used for high-temperature pyrolysis treatment, the first gradient heating rate was 1℃ / min, the target temperature was 400℃, and it was kept warm for 1h, the second gradient heating rate was 5℃ / min, the target temperature was 1000℃, and it was kept warm for 1h, and it was cooled to room temperature and taken out to obtain nitrogen-sulfur doped lignin-based foam carbon 1.
[0060] Embodiment 2:
[0061] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm, and then 200 mesh screening was performed. At room temperature, ammonium sulfate and the above-mentioned low glass transition temperature lignin powder were mixed at a high speed of 10000 rpm / min in a grinder at a mass ratio of 3:1 for 3 times, each time for 30 seconds, and stayed for 2 minutes. Then grind and mix evenly at a high speed of 10000 rpm / min for 4 times, each time for 30 seconds, and stayed for 3 minutes to obtain a mixture of ammonium sulfate and lignin; the total mass of 4g of the mixture was transferred to a crucible, evenly laid and compacted to ensure a smooth surface, the top of the crucible was sealed with tin foil and a few channels were made, and it was placed in a muffle furnace air atmosphere for heat pretreatment, and two gradient heating modes were set. The first gradient target temperature was 150°C, kept warm for 1h, and the second gradient target temperature was 280 ℃, keep warm for 2h, the heating rate is 1℃ / min, take out after cooling, and obtain an integrated lignin-based thermal pretreatment product; the integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with argon atmosphere for heating, and high-temperature pyrolysis treatment is carried out using two gradient heating modes, the first gradient heating rate is 1℃ / min, the target temperature is 400℃, and it is kept warm for 1h, the second gradient heating rate is 5℃ / min, the target temperature is 1000℃, and it is kept warm for 1h to obtain nitrogen-sulfur doped lignin-based foam carbon 2.
[0062] Embodiment 3:
[0063] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into a uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm. Then, 200 mesh screening was performed. At room temperature, ammonium sulfate and the above low glass transition temperature lignin powder were mixed at a high speed of 10,000 rpm / min in a grinder at a mass ratio of 2:1 for 3 times, each mixing for 30 seconds, and the mixture was kept for 2 minutes in between. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, each time mixing for 30s, and staying for 3min in between to obtain a mixture of ammonium sulfate and lignin; transfer 4g of the mixture to a crucible, evenly spread and compact, ensure the surface is flat, seal the top of the crucible with tin foil and make a few holes, place it in a muffle furnace air atmosphere for heat pretreatment, set two gradient heating modes, the first gradient target temperature is 150℃, keep warm for 1h, the second gradient target temperature is 280℃, keep warm for 2h, the heating rate is 1℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product; the integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with argon atmosphere for heating, and high-temperature pyrolysis treatment is carried out in a one-step heating mode, with a target temperature of 1000℃, keep warm for 2h, and a heating rate of 5℃ / min to obtain nitrogen-sulfur doped lignin-based foam carbon 3.
[0064] Embodiment 4:
[0065] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into a uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm. Then, 200 mesh screening was performed. At room temperature, ammonium sulfate and the above low glass transition temperature lignin powder were mixed at a high speed of 10000 rpm / min in a grinder at a mass ratio of 3:1 for 3 times, each time for 30 seconds, and the mixture was kept for 2 minutes. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, each time mixing for 30s, and staying for 3min in between to obtain a mixture of ammonium sulfate and lignin; transfer 4g of the mixture to a crucible, evenly lay and compact it to ensure a flat surface, seal the top of the crucible with tin foil and make a few holes, place it in a muffle furnace in an air atmosphere for thermal pretreatment, set three gradient heating modes, the first gradient target temperature is 150℃, keep warm for 1h, the second gradient target temperature is 280℃, keep warm for 2h, the heating rate is 1℃ / min, the third gradient target temperature is 400℃, keep warm for 1h, the heating rate is 5℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product; the integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with an argon atmosphere for heating, and a one-step heating mode is used for high-temperature pyrolysis treatment, with a target temperature of 1000℃, keep warm for 2h, and a heating rate of 5℃ / min to obtain nitrogen-sulfur doped lignin-based foam carbon 4.
[0066] Embodiment 5:
[0067] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into a uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm. Then, 200 mesh screening was performed. At room temperature, ammonium sulfate and the above low glass transition temperature lignin powder were mixed at a high speed of 10,000 rpm / min in a grinder at a mass ratio of 2:1 for 3 times, each mixing for 30 seconds, and the mixture was kept for 2 minutes in between. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, each time mixing for 30s, and staying for 3min in between to obtain a mixture of ammonium sulfate and lignin; transfer the mixture with a total mass of 3g to a crucible, evenly lay and compact it to ensure a flat surface, seal the top of the crucible with tin foil and make a few holes, place it in a muffle furnace in an air atmosphere for thermal pretreatment, set three gradient heating modes, the first gradient target temperature is 150℃, keep warm for 1h, the second gradient target temperature is 280℃, keep warm for 2h, the heating rate is 1℃ / min, the third gradient target temperature is 400℃, keep warm for 1h, the heating rate is 5℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product; the integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with a carbon dioxide atmosphere for heating, and a one-step heating mode is used for high-temperature pyrolysis treatment, with a target temperature of 900℃, keep warm for 1h, and a heating rate of 5℃ / min to obtain nitrogen-sulfur doped lignin-based foam carbon 5.
[0068] Embodiment 6:
[0069] The difference from Example 1 is that a total mass of 6 g of the mixture is transferred to a crucible for thermal pretreatment to obtain nitrogen-sulfur doped lignin-based foam carbon 6.
[0070] Embodiment 7:
[0071] The difference from Example 2 is that a total mass of 8 g of the mixture is transferred to a crucible for thermal pretreatment to obtain nitrogen-sulfur doped lignin-based foam carbon 7.
[0072] Embodiment 8:
[0073] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into a uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm. Then, 200 mesh screening was performed. At room temperature, ammonium chloride and the above low glass transition temperature lignin powder were mixed at a high speed of 10000 rpm / min in a grinder at a mass ratio of 2:1 for 3 times, each mixing for 30 seconds, and the mixture was kept for 2 minutes in between. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, each time for 30s, and stay for 3min in the middle to obtain a mixture of ammonium chloride and lignin; transfer 3g of the mixture to a crucible, evenly lay and compact, ensure the surface is flat, seal the top of the crucible with tin foil and make a few holes, place it in the air atmosphere of a muffle furnace for heat pretreatment, set two gradient heating modes, the first gradient target temperature is 160℃, keep warm for 1h, the second gradient target temperature is 320℃, keep warm for 2h, the heating rate is 5℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product. The above-mentioned integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with an argon atmosphere for heating, and a one-step heating mode is used for high-temperature pyrolysis treatment, with a target temperature of 1000℃, keeping warm for 2h, and a heating rate of 5℃ / min to obtain nitrogen-doped lignin-based foam carbon 8.
[0074] Embodiment 9:
[0075] The single component of low glass transition temperature lignin was dried in a constant temperature drying oven at 50°C and then ball-milled into uniform powder. The ball-milling time was 10 minutes and the ball-milling speed was 500 rpm. Then, 200 mesh screening was performed. At room temperature, ammonium dihydrogen phosphate and the above low glass transition temperature lignin powder were mixed at a high speed of 10,000 rpm / min in a grinder at a mass ratio of 4:1 for 3 times, each mixing for 30 seconds, and the mixture was stopped for 2 minutes. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, each time for 30s, and stay for 3min in the middle to obtain a mixture of ammonium dihydrogen phosphate and lignin; transfer 5g of the mixture to a crucible, evenly lay and compact, ensure the surface is flat, seal the top of the crucible with tin foil and make a few holes, place it in the air atmosphere of a muffle furnace for heat pretreatment, set two gradient heating modes, the first gradient target temperature is 230℃, keep warm for 1h, the second gradient target temperature is 360℃, keep warm for 2h, the heating rate is 3℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product. The above-mentioned integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with an argon atmosphere for heating, and a one-step heating mode is used for high-temperature pyrolysis treatment, with a target temperature of 1000℃, keeping warm for 2h, and a heating rate of 5℃ / min to obtain nitrogen and phosphorus doped lignin-based foam carbon 9.
[0076] Comparative Example 1:
[0077] According to the records of Wangda Q. et al. (Reference: Wangda Q.; Zizhu Z.; Chen L.; Pengyu H.; Zhongyi M.; Simple, additive-free, extra pressure-free process to directly convert lignin into carbon foams, International Journal of Biological Macromolecules 209 (2022) 692-702), a lignin-based carbon material was prepared from lignin with a glass transition temperature of 78°C by a heat treatment method.
[0078] Comparative Example 2:
[0079] The single component of lignin with low glass transition temperature was dried in a constant temperature drying oven at 50°C and then ball-milled into uniform powder. The ball-milling time was 10min and the ball-milling speed was 500rpm, and then 200 mesh screening was performed. At room temperature, 1g of lignin was evenly ground with a mortar, transferred to a crucible, evenly laid and compacted to ensure a flat surface. The top of the crucible was sealed with tin foil and a few self-made channels were placed in a muffle furnace in an air atmosphere for thermal pretreatment. The one-step heating mode was set, the target temperature was 280°C, the temperature was kept for 3h, the heating rate was 1°C / min, and it was taken out after cooling to obtain an integrated lignin-based thermal pretreatment product. The above-mentioned integrated lignin-based thermal pretreatment product was directly placed in a tubular furnace with an argon atmosphere for heating, and a high-temperature pyrolysis treatment was performed using a one-step heating mode. The target temperature was 1000°C, the temperature was kept for 2h, and the heating rate was 5°C / min to obtain lignin-based foam carbon 1.
[0080] Comparative Example 3:
[0081] The single component of lignin with low glass transition temperature was dried in a constant temperature drying oven at 50°C and then ball-milled into uniform powder. The ball-milling time was 10 min and the ball-milling speed was 500 rpm, and then 200 mesh screening was performed. 1 g of lignin was evenly ground with a mortar at room temperature, transferred to a crucible, evenly laid and compacted to ensure a flat surface, the top of the crucible was sealed with tin foil and a few self-made channels, and placed in a muffle furnace air atmosphere for thermal pretreatment. Two gradient heating modes were set, the first gradient target temperature was 150°C, and the heat preservation was 1h. The second gradient target temperature was 280°C, and the heat preservation was 2h. The heating rate was 1°C / min. After cooling, it was taken out to obtain an integrated lignin-based thermal pretreatment product. The integrated lignin-based thermal pretreatment product was directly placed in a tubular furnace with an argon atmosphere for heating, and high-temperature pyrolysis treatment was carried out using two gradient heating modes. The first gradient heating rate was 1°C / min, the target temperature was 400°C, and the insulation was 1h. The second gradient heating rate was 5°C / min, the target temperature was 1000°C, and the insulation was 1h to obtain lignin-based foam carbon 2.
[0082] Comparative Example 4:
[0083] Alkali lignin with a glass transition temperature of about 170℃, an industrial by-product of a paper mill in Shandong, was used as raw material. After being dried at 50℃ in a constant temperature drying oven, it was ball-milled into uniform powder. The ball-milling time was 10min and the ball-milling speed was 500rpm. Then it was screened with 200 mesh. At room temperature, the treated lignin and ammonium sulfate were mixed in a grinder at a mass ratio of 6:1 for 3 times at a speed of 10000rpm / min, each time for 30s, and stayed for 2min. Then grind and mix evenly at a speed of 10000rpm / min for 4 times, each time for 30s, and stayed for 3min to obtain a mixture; 3.5g of the mixture was transferred to a crucible, evenly laid and compacted to ensure a smooth surface. The top of the crucible was sealed with tin foil and a few channels were made by themselves. It was placed in a muffle furnace air atmosphere for thermal pretreatment. The one-step heating mode was set, the target temperature was 320℃, the temperature was kept for 3h, the heating rate was 5℃ / min, and it was taken out after cooling to obtain an integrated lignin-based thermal pretreatment product. The above-mentioned integrated lignin-based thermal pretreatment product was directly placed in a tubular furnace with an argon atmosphere for heating, and a high-temperature pyrolysis treatment was performed in a one-step heating mode with a target temperature of 1000°C, a heat preservation time of 2h, and a heating rate of 5°C / min to obtain lignin-based foam carbon 3.
[0084] Comparative Example 5:
[0085] The enzymatic lignin with a glass transition temperature of about 160°C, an industrial byproduct of a biorefining company in Shandong, was used as raw material. After being dried in a constant temperature drying oven at 50°C, it was ball-milled into uniform powder. The ball-milling time was 10 minutes, the ball-milling speed was 500 rpm, and then 200 mesh screening was performed. The treated lignin and ammonium sulfate were mixed at a mass ratio of 1:1 at room temperature in a grinder at a speed of 10,000 rpm / min for 3 times, each mixing for 30 seconds, and the intermediate stay was 2 minutes. Then grind and mix evenly at a high speed of 10000rpm / min for 4 times, mix for 30s each time, and stay for 3min in the middle to obtain a mixture; transfer 4g of the mixture to a crucible, evenly lay and compact, ensure the surface is flat, seal the top of the crucible with tin foil and make a few holes, place it in a muffle furnace air atmosphere for heat pretreatment, set a one-step heating mode, the target temperature is 320℃, keep warm for 2h, the heating rate is 10℃ / min, take it out after cooling, and obtain an integrated lignin-based thermal pretreatment product. The above-mentioned integrated lignin-based thermal pretreatment product is directly placed in a tubular furnace with an argon atmosphere for heating, and a high-temperature pyrolysis treatment is carried out in a one-step heating mode, with a target temperature of 1000℃, keeping warm for 2h, and a heating rate of 5℃ / min to obtain lignin-based foam carbon 4.
[0086] Comparative Example 6:
[0087] The difference from Example 9 is that at room temperature, ammonium dihydrogen phosphate and the above-mentioned low glass transition temperature lignin powder are mixed in a grinder at a mass ratio of 1:1 at a high speed of 10000 rpm / min to obtain lignin-based foam carbon 5.
[0088] Application Example 1:
[0089] The two nitrogen-sulfur doped lignin-based foam carbons 1 in the above-mentioned Example 1 are symmetrically matched and assembled into a capacitive deionization module. The capacitive deionization desalination module consists of only two integrated lignin-based foam carbon electrodes, a salt solution, and a liquid storage tank; a peristaltic pump is used to circulate the salt solution in the liquid storage tank, and a conductivity probe is used to monitor the conductivity of the salt solution in real time in the water reservoir; the symmetrical capacitive deionization module and the DC voltage circuit form a closed loop, and the DC voltage is 1.6V; the NaCl solution concentration is 780mg / L, the volume is 100mL, and the flow rate is 15mL / min. A conductivity probe is used to monitor the conductivity changes of the NaCl solution in real time in the water reservoir. The adsorption time is 60min, and then the voltage is set to 0V for desorption, and the desorption time is 30min. The results are as follows Fig.13 shown.
[0090] Application Example 2:
[0091] The nitrogen-sulfur doped lignin-based foam carbon 3 in Example 2 was polished with sandpaper into a size of 1×1 cm 2, with a thickness of about 1.8 mm, and directly used it as a self-supporting working electrode, 1ⅹ1cm 2 The Pt electrode was used as the reference electrode, the Ag / AgCl (saturated KCl solution) electrode was used as the counter electrode, and the 1M NaCl solution was used as the electrolyte. The electrochemical performance of the supercapacitor was tested using a three-electrode system. The cyclic voltammetry test was performed in the voltage range of 0-1V and the scanning rates of 1, 2, and 5mV / s. The constant current charge and discharge test was performed in the voltage range of 0-1V and the currents of 0.2, 0.5, and 1.0Ag. -1 The results are as follows Figure 3 shown.
[0092] Application Example 3:
[0093] The nitrogen-sulfur doped lignin-based foamed carbon 5 in Example 5 and the lignin-based foamed carbon 2 in Comparative Example 3 were respectively polished with sandpaper into a size of 1×1 cm 2 , thickness of about 1.8mm, and directly use it as a self-supporting work, 1ⅹ1cm 2 The Pt electrode was used as the reference electrode, the Ag / AgCl (saturated KCl solution) electrode was used as the counter electrode, and the 1M NaCl solution was used as the electrolyte. The electrochemical performance of the supercapacitor was tested using a three-electrode system. The cyclic voltammetry test was performed in the voltage range of 0-1V and the scan rate of 2mV / s. The results are shown in Figure 8 shown.
[0094] Test results:
[0095] Figure 1 The sample provided in Example 1 of the present invention is shown in the figure. The left side shows the product of thermal pretreatment, and the right side shows the product after high-temperature pyrolysis. Figure 1 It can be seen that the products on the left and right sides are in regular cubic block structures. Due to the thermal decomposition of ammonium sulfate and lignin, carbon cross-linking and other reactions during the high-temperature pyrolysis process, the size of the product on the right side becomes smaller, but the high-temperature pyrolysis does not damage the macroscopic morphology and self-supporting structure. Figure 7 a), the macroscopic regular structure of the product was significantly improved, indicating that ammonium sulfate significantly improved the excessive foaming of lignin.
[0096] Figure 2 This is a physical picture of the sample of Example 2 of the present invention. The left side is the thermal pretreatment product, and the right side is the physical picture of the product after high-temperature pyrolysis. It can be seen that the products on both the left and right sides have regular cubic block structures, which is conducive to the application of lignin-based carbon materials in supercapacitors, capacitive deionization, etc.
[0097] Figure 3(a) Cyclic voltammetry curve and (b) constant current charge-discharge curve of the pyrolysis product of Example 2 in Application Example 2 of the present invention. Figure 3 It can be seen that the ammonium sulfate-modified and doped low glass transition temperature lignin-based foam carbon as a self-supporting electrode exhibits good electrochemical double layer characteristics and symmetry. The mass specific capacity at current densities of 0.2, 0.5, and 1 A / g are 146, 106, and 62 F / g, respectively, indicating that ammonium sulfate doping is helpful for the application of lignin-based foam carbon in supercapacitors and other aspects.
[0098] Figure 4 The physical picture of the high temperature pyrolysis product of the present invention, wherein the left side is the high temperature pyrolysis product of Example 6, and the right side is the physical picture of the high temperature pyrolysis product of Example 7. Figure 4 It can be seen that even if the feed amount is doubled and then subjected to heat pretreatment, a regular foam carbon integral structure with a relatively large thickness can still be formed.
[0099] Figure 5 This is a physical picture of the thermal pretreatment product of Example 8 of the present invention, from Figure 5 It can be seen that ammonium chloride doping can significantly improve the excessive foaming phenomenon of lignin, and can achieve the preparation of lignin-based foam carbon with a thin thickness of millimeter level and a size of centimeter level, and has a good self-supporting overall structure.
[0100] Figure 6 The SEM images of the products of the present invention are shown in Figure 2, wherein (a) is the SEM image of the product in Example 3, and (b) is the SEM image of the product in Comparative Example 2. Figure 6 It can be seen that the pore size of the product in Comparative Example 2 reaches hundreds of microns, while the lignin-based foam carbon after ammonium sulfate doping in Example 3 has a rich pore structure, a significantly reduced pore size, and still presents a good continuous carbonaceous network structure. Usually, when preparing foam carbon with a single component lignin as a raw material, a one-step heating method is usually used in the thermal pretreatment stage to prepare foam carbon with a regular morphology. However, the SEM image of Comparative Example 2 shows that for low glass transition temperature lignin, even at a temperature of 280°C and a low heating rate of 1°C / min, the product still has excessive foaming, which indicates that low glass transition temperature lignin-based foam carbon has serious excessive foaming under conventional preparation conditions.
[0101] Figure 7 The physical pictures of the products of comparative example 3 of the present invention at different angles, (ac) are the products of thermal pretreatment, (d, e) are the products of high temperature pyrolysis, Figure 7 It can be seen that the thermal pretreatment product has significant bubbling phenomenon. Although it is a self-supporting structure, it is fragile and the pore size is clearly visible to the naked eye, reaching hundreds of microns or even millimeters. After high-temperature pyrolysis, the surface of the product has a metallic luster, and the excessive foaming phenomenon still exists.
[0102] Figure 8 The cyclic voltammetry curves of the high temperature pyrolysis product as a self-supporting electrode at a scanning rate of 2 mV / s in Example 5 and Comparative Example 3 of the present invention are shown in FIG. Figure 5 It can be seen that the nitrogen-sulfur doped self-supporting lignin-based hierarchical porous defect-rich foam carbon prepared in Example 5 has good double electrical layer properties, about 156F / g, while the undoped lignin-based foam carbon electrode in Comparative Example 3 has almost no specific capacity.
[0103] Fig. 9 The mechanical strength of the products after high temperature pyrolysis in Example 6 and Example 7 of the present invention is compared with that in Comparative Example 3. The mechanical strengths of the three samples are 590, 870, and 230 kPa, respectively. The mechanical strength of the sample prepared in Comparative Example 3 is significantly lower than that of the samples prepared in Example 6 and Example 7, which indicates that the pore structure of the lignin-based foamed carbon is well distributed and the carbon skeleton is more dense after doping.
[0104] Fig.10 This is a SEM image of the heat pretreatment product in Comparative Example 4 of the present invention. The glass transition temperature of the lignin used is greater than 150°C, and the lignin is in granular form. According to the current research status, higher heat pretreatment temperature (320°C) and heating rate (5°C / min) are beneficial for the foaming of lignin-based foamed carbon. However, this Comparative Example 4 only adds about 14.3wt% of ammonium sulfate. Even if the temperature is increased to 320°C and the heating rate is accelerated to 5°C / min, the product is still in the original lignin granular form. The results show that even if a small amount of ammonium sulfate is added, the glass transition temperature of this type of lignin may still be increased, which is not conducive to good softening and fusion behavior between this type of lignin particles. For the low glass transition temperature lignin in Examples 1-3, at a low heat pretreatment temperature of 280°C, the heating rate is only 1°C / min, and the ammonium sulfate ratio reaches 66.7wt% or more to better suppress excessive foaming of the product.
[0105] Fig.11 This is a SEM image of the high-temperature pyrolysis product in Comparative Example 5 of the present invention. The glass transition temperature of the lignin used is greater than 150° C., and incomplete softening and fusion behavior occur between the lignin particles.
[0106] Fig.12 This is a physical picture of the product of Comparative Example 6 of the present invention. Fig.12 It can be seen that the lignin-based foamed carbon 5 obtained in Comparative Example 6 still has the phenomenon of excessive foaming, indicating that the mass ratio of diammonium phosphate to the above-mentioned lignin powder with a low glass transition temperature is too low.
[0107] Fig.13 This is the curve of NaCl solubility (TDS) of the high temperature pyrolysis product of Example 1 as a self-supporting electrode in capacitive deionization as a function of adsorption and desorption time. Fig.13It can be seen that during the adsorption process, as the adsorption time increases, Na + , Cl - Gradually adsorbed onto the electrode, the TDS in the solution gradually decreases, achieving the purpose of desalination. During the desorption process, as the desorption time increases, the Na + , Cl - When it is returned to the solution, TDS gradually increases, achieving the purpose of electrode regeneration. When the salt concentration is 780 mg / L, the area adsorption capacity is about 0.14 mg / cm 2 .
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element, characterized in that: The method comprises the following steps: (1) Selecting lignin with a low glass transition temperature as a raw material; the lignin with a low glass transition temperature in step (1) is lignin with a glass transition temperature lower than 150°C; (2) low-temperature drying the low glass transition temperature lignin in step (1), grinding it into a granular homogeneous powder, and sieving it for subsequent use; (3) weighing a certain amount of ammonium salt and the lignin powder treated in step (2), uniformly mixing them, and grinding them into granular homogeneous powder to obtain a mixture of ammonium salt and lignin; the mass ratio of the ammonium salt in step (3) to the lignin powder treated in step (2) is (1-5):1; (4) placing the mixture of ammonium salt and lignin in step (3) in a crucible or a mold, evenly laying and compacting it to ensure that the surface is flat, sealing the top of the crucible or the mold with tin foil or making a few holes by yourself, performing heat pretreatment, and taking it out after cooling to obtain a heat pretreated product; the heat pretreatment heating method in step (4) is a one-step heating mode, a two-gradient heating mode or a multi-gradient heating mode; the target temperature of the one-step heating mode in step (4) is 240-550°C, and the insulation time is 1-3h; or, the two-gradient heating mode in step (4) is a first gradient target temperature of 100-240°C, the insulation time is 0.5-2h, and the second gradient target temperature is 240-350°C, and the insulation time is 0.5-2h; or, the multi-gradient heating mode in step (4) is a three-gradient heating mode, and the three-gradient heating mode is a first gradient target temperature of 100-240°C, the insulation time is 0.5-2h, and the second gradient target temperature is 240-350°C, and the insulation time is 0.5-2h; ℃, insulation time 0.5~2h, the second gradient target temperature is 240~350 ℃, insulation time 0.5~2h, the third gradient target temperature is 360~550 ℃, insulation time 0.5~2h; (5) The pretreatment product of step (4) is subjected to high-temperature pyrolysis treatment under a certain atmosphere, and is taken out after being cooled to room temperature to obtain a self-supporting lignin-based foam carbon doped with heterogeneous non-metallic elements and modified; the high-temperature pyrolysis method in step (5) is a one-step heating mode or a two-gradient heating mode; the high-temperature pyrolysis in step (5) is a one-step heating mode, and the target temperature of the one-step heating mode is 600-1200°C; or, the high-temperature pyrolysis in step (5) is a two-gradient heating mode, and the first gradient target temperature in the two-gradient heating mode is 300-500°C, and the second gradient target temperature is 600-1200°C.
2. The method for preparing a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element according to claim 1, characterized in that: In the step (2), the grinding is performed by ball milling, the ball milling time is 10 min to 60 min, and the ball milling speed is 300 to 1000 r / min.
3. The method for preparing a self-supporting lignin-based foam carbon doped with a heterogeneous non-metallic element according to claim 1, characterized in that: The ammonium salt in step (2) is any one or more of ammonium borate, ammonium sulfate, ammonium chloride, diammonium phosphate or a mixture of ammonium phosphate.
4. The method for preparing a self-supporting lignin-based foamed carbon doped with a heterogeneous non-metallic element according to claim 1, characterized in that: The atmosphere in step (5) is nitrogen, argon, carbon dioxide, ammonia or water vapor.
5. A lignin-based carbon foam material obtained by processing according to the method for preparing a self-supporting lignin-based carbon foam modified by doping with a heterogeneous non-metallic element as described in any one of claims 1 to 4.
6. Use of the lignin-based foamed carbon according to claim 5 in the fields of supercapacitors, lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, electromagnetic wave absorption, heavy metal ion adsorption or catalysis.
7. Use of the lignin-based foamed carbon according to claim 6 in capacitive deionization of seawater or brackish water.
Citation Information
Patent Citations
Fast cure and pre-cure resistant cross-linked phenol-formaldehyde adhesives and methods of making same
CA2042476A1
Flexible self-supported porous carbon @ layered bimetallic hydroxide composite material, its preparation method and application
CN106328385A
Porous foam carbon and preparation method thereof
CN108557801A
Preparation method of lignin-based N-doped carbon aerogel
CN109277082A
Method for preparing foam carbon through lignin self-foaming
CN112897507A
